A South African Perspective on Inclusive Education Conceptualisation and Impact on Practices (European Journal of Teaching and Education, 2025)
This study explores the impact of primary school principals and Foundation Phase teachers' conceptualisations of inclusive education on their teaching practices in South Africa. The importance of these conceptualisations is emphasised because they have a direct bearing on the daily teachers’ practices in the classroom and, in the end, define the degree of inclusion that learners encounter. The goal is to find out how primary school principals and teachers perceive inclusive education and examine how their perceptions influence the pedagogical decisions they make. A qualitative transformative approach was employed using individual semi-structured interviews and focus group discussions to collect data from thirteen Foundation Phase teachers and three primary school principals from Johannesburg South government schools. Data were analysed through inductive and deductive thematic analysis, drawing support from the Inclusive Pedagogical Approach (IPA) and Bronfenbrenner’s Ecological Systems Theory. The findings reveal three distinct stages of pedagogical development toward inclusivity among participants, elaborating on Black-Hawkins' (2017) model of a single required shift. These stages range from "no shift”, “little/emerging shift” to "established shift," with each stage characterised by specific conceptualisations that influence teaching strategies. The study concludes that these varying levels of development contribute to the challenges of implementing inclusive education effectively. Consequently, the study recommends targeted support based on a teacher's identified developmental stage. Those with no shift require awareness training on IE policies and practices, while those exhibiting an emerging shift benefit from encouragement and support to achieve full inclusivity. Teachers with an established shift can further refine and maintain their inclusive practices.